Analisis Rencana Pelaksanaan Pembelajaran Tematik di Kelas V Sekolah Dasar Negeri 16 Pontianak Kota - Cici Oktria Ningsih; Kartono Kartono; Dyoty Auliya Vilda Ghasya (Departement of Mathematics Education, 2023)
This study aims to describe the plan for implementing thematic learning by the fifth grade teacher at SD Negeri 16 Pontianak Kota. The research method used is descriptive with a qualitative research form. Sources of research data were obtained from class V teachers at SD Negeri 16 Pontianak. The data in this study are in the form of thematic learning implementation plan documents as well as the results of interviews and questionnaires. The data analysis used in this study is the Miles and Huberman model. To test the credibility of the data on the research results using triangulation of data collection techniques, namely by checking the data to the same source with different techniques. The techniques used are documentation, interviews, and questionnaires. The results of the analysis show that the thematic learning implementation plan by the teacher is complete, but the accuracy of the content in each component of the thematic learning implementation plan which is guided by the minister of education regulation number 22 of 2016 concerning process standards made by the teacher is not completely correct. In making learning implementation plans there are several difficulties, namely formulating learning objectives, determining operational verbs, and making learning activities.